2020
DOI: 10.1101/2020.04.22.20076091
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gut microbiota may underlie the predisposition of healthy individuals to COVID-19

Abstract: 1The COVID-19 pandemic is spreading globally with high disparity in the 2 susceptibility of the disease severity. Identification of the key underlying factors for 3 this disparity is highly warranted. Here we describe constructing a proteomic risk 4 score based on 20 blood proteomic biomarkers which predict the progression to 5 severe COVID-19. We demonstrate that in our own cohort of 990 individuals without 6 infection, this proteomic risk score is positively associated with proinflammatory 7 cytokines mainly… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
167
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(175 citation statements)
references
References 35 publications
2
167
0
6
Order By: Relevance
“…Due to their immunomodulatory properties, postbiotics could also be explored as a novel therapeutic approach for the prevention and treatment of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). A recent study proposed the role of the microbiome in the development of severe cases of coronavirus disease 2019 (COVID-19) [ 135 ], while others suggested that metabolites produced by the intestinal microbiome could be used for developing a drug for individuals who are susceptible to SARS-CoV-2 infection [ 136 , 137 ]. However, well controlled studies in humans are urgently needed to demonstrate whether postbiotics would have any effect against these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their immunomodulatory properties, postbiotics could also be explored as a novel therapeutic approach for the prevention and treatment of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). A recent study proposed the role of the microbiome in the development of severe cases of coronavirus disease 2019 (COVID-19) [ 135 ], while others suggested that metabolites produced by the intestinal microbiome could be used for developing a drug for individuals who are susceptible to SARS-CoV-2 infection [ 136 , 137 ]. However, well controlled studies in humans are urgently needed to demonstrate whether postbiotics would have any effect against these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Postbiotics may also be useful in the prevention and treatment of SARS-CoV-2 infection, as the structure and metabolic activity of the intestinal microbiome may be related to the occurrence of biomarkers predicting the severe coronavirus disease 2019 (COVID-19) course [106].…”
Section: Future Clinical Applicationsmentioning
confidence: 99%
“…Changes in the balance of the gut microbiome (dysbiosis) are associated with a greater susceptibility to diseases and opportunistic infections, due to the decrease in the protective microbial load of symbiotic bacteria, which can lead to dysregulation of the immune system and to autoimmune diseases ( 4 ). Such changes were also found to be correlated with COVID-19 prognosis ( 5 , 6 ). Yet there are no data on the effect of human behavior during the COVID-19 pandemic on the gut microbiota.…”
Section: Perspectivementioning
confidence: 70%